Single-dose intravenous administration of antiepileptic drugs induces rapid and reversible remodeling in the brain: Evidence from a voxel-based morphometry evaluation of valproate and levetiracetam in rhesus monkeys - Tang, Y.; Yu, X.; Zhang, X.; Xia, W.; Wu, X.; Zou, X.; Li, H.; Huang, X.; Stefan, Hermann; Chen, Q.; Gong, Q.; Zhou, D. (Neuroscience, 2015)
Effects of the long-term use of antiepileptic drugs (AEDs) on the brains of patients with epilepsy have been previously reported. The aim of this study was to determine the rapid brain structure remodeling induced by single-dose intravenous AED administration that rules out the potential effects of epilepsy.Ten rhesus monkeys were randomly divided into two groups and were intravenously administered a single dose of valproic acid (VPA) or levetiracetam (LEV) at treatment dosages. Magnetic resonance imaging (MRI) data were recorded from every subject prior to AED administration and at 2h and 1 week after administration. Using optimized voxel-based morphometry (VBM) analysis, we measured changes in regional gray matter volume (GMV) and white matter volume (WMV) in each group over time following medication and directly compared the differences between the two groups.Both AEDs induced brain volume alterations at 2h after their administration, but these changes had reverted at 1 week. The VPA group exhibited increased GMV in the right geniculate nucleus and the right pulvinar, whereas the LEV group exhibited WMV reductions in the right pulvinar, the right parietal lobe and the right occipital lobe. Directly compared with the LEV group, the VPA group exhibited a temporally constant GMV increase in the bilateral temporal cortex and a WMV reduction in the left pedunculus cerebri.Single-dose intravenous administration of a level of VPA or LEV that mimics clinical use is associated with rapid and reversible VBM-detected GMV or WMV alterations in rhesus monkeys. This finding may provide new insights into the understanding of AED-induced brain structure remodeling and may contribute to our understanding of the brain-level mechanisms and targets of AED action.
EVALuna2:22417